Development of an Evaluation Framework Suitable for Assessing Humanitarian Workforce Competencies During Crisis Simulation Exercises. Issue 1 (15th January 2014) - Cranmer, Hilarie; Chan, Jennifer L.; Kayden, Stephanie; Musani, Altaf; Gasquet, Philippe E.; Walker, Peter; Burkle, Frederick M.; Johnson, Kirsten
Abstract: The need to provide a professionalization process for the humanitarian workforce is well established. Current competency-based curricula provided by existing academically affiliated training centers in North America, the United Kingdom, and the European Union provide a route toward certification. Simulation exercises followed by timely evaluation is one way to mimic the field deployment process, test knowledge of core competences, and ensure that a competent workforce can manage the inevitable emergencies and crises they will face. Through a 2011 field-based exercise that simulated a humanitarian crisis, delivered under the auspices of the World Health Organization (WHO), a competency-based framework and evaluation tool is demonstrated as a model for future training and evaluation of humanitarian providers. H Cranmer, J Chan, S Kayden, A Musani, P Gasquet, P Walker, F Burkle, K Johnson .Development of an evaluation framework suitable for assessing humanitarian workforce competencies during crisis simulation exercises .Prehosp Disaster Med .2014 ;29 (1 ):1 -6 .